Pneumotoraks spontan primer berulang pada wanita hamil dengan hiperemesis gravidarum: laporan kasus - Ni Putu Ayu Widiasari; Ni Luh Putu Eka Arisanti; Ida Bagus Ngurah Rai (DiscoverSys Inc., 2019)
Background: Spontaneous pneumothorax is a rare case during pregnancy. However, the condition of Hyperemesis Gravidarum during pregnancy is one of the risk factors for recurrent primary spontaneous pneumothorax.Case Description: A 28-year-old woman with G5P3013 gestational age 12-13 weeks with Hyperemesis Gravidarum had complaints of tightness and recurrent acute pleuritic chest pain. After a clinical and supporting examination using ultrasound, patients were diagnosed with recurrent primary spontaneous pneumothorax, and observational and symptomatic treatments were performed. The rupture of the bleb or the subpleura bulla is thought to be a pathological mechanism. Patients given birth vaginally without complications and complete resolution of the pneumothorax occurred.Conclusion: Recurrent pneumothorax in pregnant women with a history of hyperemesis gravidarum is rare. Observational and symptomatic treatment is the initial treatment that can be done.